Le terrecotte della collezione di Raffaele Gargiulo al Museo Archeologico Nazionale di Napoli - Riccardo Berriola (Les Carnets de l’ACoSt)
The collection of terracottas belonging to Raffaele Gargiulo that was purchased by the Museum of Naples in 1855 was accompanied by a rich assortment of architectural terracotta fragments, pottery, plastic vases, and lamps, among other objects. Of these objects, the terracottas are in the majority (73.88%) and account for about three-quarters of the entire collection. Five hundred seventy-eight of these terracottas (95.54%) come from Apulia and Campania, areas that are well known for their coroplastic production. While the architectural terracottas date from the end of the 4th century B.C.E. to the first century C.E., the chronological range of the majority of the figurines and pottery is more limited and can be placed between the mid-4th and the end of the 3rd century B.C.E. The chronology of the plastic vessels is broader and ranges from the late 6th to the 3rd century B.C.E., with lamps dated to the 1st century C.E.